Genotypic variation in nitrogen fixation characteristics in faba bean (Vicia faba L.) under contrasting phosphorus fertilizer regimes - Gemechu Abu; Victor Adetimirin; Christian Fatokun; Gemechu Keneni; Fassil Assefa (Agrosystems, Geosciences & Environment)
Abstract Assessment of the genetic variability is an important step in improving nitrogen (N2) fixation potential of faba bean (Vicia faba L.) genotypes. The study was conducted to evaluate the genotypic variation for symbiotic N2 fixation traits of faba bean under contrasting phosphorus (P) fertilizer regimes. Twenty and 12 genotypes in the field and greenhouse, respectively, were planted under two P fertilizer regimes (P− and P+ corresponding to 0 and 46 kg/ha) using a randomized complete block design with three replications. Analysis of variance indicated highly significant (p < 0.01) variation among genotypes for all N2 fixation traits under both P regimes, indicating the availability of genotypic variation. Genotypes Obse, Dosha, Didea, Gebelcho, Gora, Moti, and Hachalu had better performance for N2 fixation traits and higher grain yield (GY) across all study conditions. Performances of all N2 fixation traits, except nitrogen harvest index, were better under P+ than under P−. P fertilizer application in the field resulted in 12.3, 12.9%, 18.9%, and 24.2% increase in the number of nodules per plant, nodule dry weight per plant (NDWP), N2 yield (NY), and the amount of N2 fixed (NF), respectively. In the greenhouse, 18.9%, 22.5%, and 27.2% increment was obtained for NDWP, NY, and NF, respectively, due to fertilizer application. Biplot analysis revealed that NF, NY, percentage of nitrogen derived from atmosphere (%Ndfa), shoot nitrogen concentration (ShN), and GY were the traits responsible for large genetic variation for N2 fixation. NF had higher heritability and formed a significant positive correlation with most nitrogen fixation traits, suggesting the potential of the trait to be improved through breeding.